ACCIDENTS AND OCCUPATIONAL ILLNESS ASSESSMENTS FOR 400/220/110/20 kV URECHESTI POWER SUBSTATION - Nicolae Daniel FÎȚĂ; Mila Ilieva OBRETENOVA; Florin MURESAN – GRECU; Gheorghe Eugen SAFTA; Adrian Mihai SCHIOPU; Dan Cristian LAZAR (Fiabilitate şi Durabilitate)
In recent decades, as a consequence of accelerated economic development, the issue of industrial and occupational risks, as well as the degree of diversification of real risks, have become increasingly important. The experience gained with accidents at work, damage and other categories of undesirable events highlights the need to understand and control risks "upstream", i.e. before the accident occurs. At the same time, awareness of populations at risk has resulted in a significant decrease in the risk acceptability threshold. In response to these social phenomena, public institutions, economic agents in the industry, researchers in the disciplines involved have proposed methods of risk forecasting, aimed at developing prevention and protection systems that improve the risk management process. Prevention of occupational risks is the only way to improve the safety and health conditions of the participants in the work process, as well as a reliable source for reducing costs, increasing labor productivity, quality of production and, finally, quality of social life. Risk management facilitates a structured and systematic approach to decision-making. The value and strength of the managerial approach to risk lies in the fact that it combines various valuation and consultation techniques, uniting them into an ensemble that gives consistency to the decision-making process. Risk management gives any organization the ability to better understand how operations are carried out and the ability to respond more effectively to changes in internal and external circumstances.